TISSUE ENGINEERING IN REGENERATIVE ENDODONTICS -A REVIEW - Janavathi, dr; Bai Rathod, Shardha; Kumar M, Naveen; Ramadevi, dr (International Journal of Clinical and Biomedical Research, 2015)
Tissue engineering is mainly used to replace the impaired or damaged tissues with new tissues. The key cells involved for tissue engineering are stem cells, the morphogens or growth factors. They will rapidly multiply and differentiates and forms tissues. This new technique is now most commonly used in endodontics. The aim of this study was to review about the dental pulp stem cells, which are most common growth factors, and the scaffolds used to control their differentiation. To study the clinical technique for the management of immature non-vital teeth based on this novel concept. KEYWORDS: Dental pulp stem cells; Morphogens; Scaffolds; Regenerative endodontics; Pulp revascularization.